Biantennary oligoglycines and glyco-oligoglycines self-associating in aqueous medium - Tsygankova, Svetlana V.; Chinarev, Alexander A.; Tuzikov, Alexander B.; Severin, Nikolai; Kalachev, Alexey A.; Rabe, Juergen P.; Gambaryan, Alexandra S.; Bovin, Nicolai V. (Beilstein Journal of Organic Chemistry, 2014)
Oligoglycines designed in a star-like fashion, so-called tri- and tetraantennary molecules, were found to form highly ordered supramers in aqueous medium. The formation of these supramers occurred either spontaneously or due to the assistance of a mica surface. The driving force of the supramer formation is hydrogen bonding, the polypeptide chain conformation is related to the folding of helical polyglycine II (PG II). Tri- and tetraantennary molecules are capable of association if the antenna length reach 7 glycine (Gly) residues. Properties of similar biantennary molecules have not been investigated yet, and we compared their self-aggregating potency with similar tri- and tetraantennary analogs. Here, we synthesized oligoglycines of the general formula R-Glyn-Х-Glyn-R (X = -HN-(СН2)m-NH-, m = 2, 4, 10; n = 1–7) without pendant ligands (R = H) and with two pendant sialoligands (R = sialic acid or sialooligosaccharide). Biantennary oligoglycines formed PG II aggregates, their properties, however, differ from those of the corresponding tri- and tetraantennary oligoglycines. In particular, the tendency to aggregate starts from Gly4 motifs instead of Gly7. The antiviral activity of end-glycosylated peptides was studied, and all capable of assembling glycopeptides demonstrated an antiviral potency which was up to 50 times higher than the activity of peptide-free glycans.
Keywords: glycopeptides; influenza virus; multivalent glycosystems; oligoglycine; polyglycine II; self-assembling; tectomers